Successful immune checkpoint inhibitor rechallenge after immune-related pericarditis: Clinical case series - Chye, Adrian M.; Nordman, Ina I. C.; Sverdlov, Aaron L. (Frontiers in Cardiovascular Medicine, 2022)
Pericardial diseases secondary to immune checkpoint inhibitors (ICI) are rare. Here, we describe two cases of immune-related pericarditis caused by ICI for treatment of advanced NSCLC. Select patients can be successfully rechallenged with ICI after immune-related pericardial disease.